âPENGARUH TIME BUDGET PRESSURE, LOCUS OF CONTROL DAN GAYA KEPEMIMPINAN TERHADAP PERILAKU DISFUNGSIONAL AUDIT DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING DI KANTOR AKUNTAN PUBLIK KOTA SEMARANGâ - Dwijayanti Rahayu, 14.05.52.0261; Jaeni, Jaeni (Students Journal of Accounting and Banking, 2018)
Dysfunctional audit behaviour is deviates behaviour from audit standards on doing audit assignments that can reduce audit quality. Dysfunctional audit behaviour can be reduced by knowing the caus factors which is from internal individu auditors. This study aims to examine the effects of time budget pressure, lcus of control, and leadership style to dysfunctional audit behaviour with organization commitment as intervening variable.Populations from this study is all of auditors who worked at audit firm in Semarang. The sample collected with convenience sampling method with total sample 98 auditors. Primary data was collected by distributing questionnaires to the responden. Data analysis using path analysis. The results from this study there is time budget pressure and locus of control has negative significant relationship on organizational commitment, positive significant relationship between leadership behavior and organizational commitment, positive significant relationship between time budget pressure and dysfunctional audit behaviour, positive not significant relationship between locus of control and dysfunctional audit behaviour while leadership behaviour and organizational commitment has no effects on dysfunctional audit behaviour. It was also found that there is no effect of mediation between time budget pressure, locus of control and leadership behaviour through organizational commitment towards dysfunctional audit behaviour.Keywords:time budget pressure, locus of control, leadership behaviour, organizational commitment and dysfunctional audit behaviour.